Hepatitis C Virus Exposure and Infection in the Perinatal Period - Varol, Mine; Licka Dieye, Ndeye; Zang, Michael; Handa, Deepali; C. Zorich, Shauna; Millen, Amy E.; Gomez-Duarte, Oscar G. (Current Pediatric Reviews, 2023)
Background: Hepatitis C virus infection is a leading cause of blood-borne hepatitis disease worldwide. Hepatitis C is a silent liver disease that, without treatment, leads to late-onset complications, including chronic hepatitis, liver cirrhosis, and hepatocellular carcinoma, in 10-40% of patients. Objective: This study aimed to review the epidemiology, clinical features, diagnosis, treatment, and prevention of hepatitis C among perinatally exposed children. Methods: Public databases, including MEDLINE and PubMed, and websites from the Centers for Disease Control and Prevention, the Food and Drug Administration, the World Health Organization, and the National Institutes of Health were searched for relevant articles published between 2006 and 2021. Results: The prevalence of hepatitis C has increased among women of childbearing age in the United States and is associated with risk factors, such as intravenous drug use, health inequities, and low socioeconomic background. Infants born to hepatitis C virus-infected mothers have a 6% risk of vertical transmission, and among those infected, 75% will develop chronic hepatitis C and late complications. However, hepatitis C-exposed infants are frequently lost to follow-up, and those infected have delayed diagnosis and treatment and are at high risk for late-onset complications. Direct- acting antivirals and the establishment of effective treatment guidelines cure hepatitis C virus infections. Conclusion: Hepatitis C predominantly affects underserved communities. Early screening of mothers and infants is critical for the diagnosis, treatment, and prevention of chronic infections and lateonset complications. New policies are needed to address hepatitis C health care inequities affecting mothers and infants in the United States.
Keywords: perinatal